ANALISIS NILAI PASAR TANAH DENGAN METODE PENDEKATAN DATA PASAR DAN PENDEKATAN BIAYA PADA PERUMAHAN VILLA TAMARA KOTA SAMARINDA DARI TAHUN 2013-2017 - -, Arjuli Asdan (EKONOMIA, 2019)
The research aims to find out whether the price of land in Villa Tamara Housing Samarinda City is determined by PT. Diyatama Persada Raya from 2013-2017 is in accordance with the market value of land with the method of market data approach and cost approach. The purpose of research based on the formulation of the problem of whether the determination of land prices at Villa Tamara Housing Samarinda by PT. Diyatama Persada Raya from 2013-2017 is in accordance with the market value of land with the method of market data approach and cost approach.The basic theory used is financial accounting that focuses on the valuation of fixed assets. Analyzer used is approach of market data and cost approach.This research show comparison between land price at Villa Tamara Housing of Samarinda City determined by PT. Diyatama Persada Raya with market value of land using market data approach and cost approach from 2013-2017. In the Year 2015 and 2016 there is no significant difference between the price of land determined by PT. Diyatama Persada Raya with the market value of the land. In 2013, 2014 and 2017 there is a very significant difference between land prices determined by PT. Diyatama Persada Raya with the market value of the land. The conclusion of this research is land price at Villa Tamara Housing of Samarinda City determined by PT. Diyatama Persada Raya from 2013-2017 does not match the market value of land with market data approach method and cost approach. The research undertaken supports the hypothesis, then the hypothesis is accepted.